A SYSTEMATIC REVIEW OF THE APPROACHES ENHANCING THE MATHEMATICS ACHIEVEMENT - Tümkaya, Songül; Ulum, Hakan (Journal of Education Culture and Society, 2020)
Aim. The aim of this study is to analyse the conducted studies in order to reveal the effect of the strategies, methods and techniques used in elementary school mathematics courses, to apply critical strategies based on impartiality, and to critically evaluate and synthesize them. Methods. In this systematic review study, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement was used in order to prepare the systematic review protocol. The studies were based on students’ achievement resulting from student-centred strategy, methods and techniques. Results. The results of the study show that the number of participants of the primary studies centred on the range of 31- 60 to 90 and above. Moreover, the total number of studies conducted in different countries constitutes a significant proportion of the studies included. In most of the studies (f=87), significant differences were found in favour of the experimental group. Conclusion. Within the framework of the inclusion criteria of the research, it can be concluded that student-centred strategy methods and techniques statistically change the students’ mathematics achievement. Among these methods and techniques, Realistic Mathematics Education, Computer Assisted Teaching Method, and Collaborative Learning Method were prominent.